Benefits of Kinesiology Tape on Tendinopathies: A Systematic Review - Miguel Ortega-Castillo; Lidia Martin-Soto; Ivan Medina-Porqueres (Montenegrin Sports Academy, 2020)
The purpose of this systematic review was to produce a best evidence synthesis of the effects of Kinesiology Tape (KT) in the treatment of tendinopathies. An electronic search on five databases (PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library, SportDiscus, and Physiotherapy Evidence Database (PEDro)) was conducted. Studies were included if (1) patients suffered from tendinopathy; (2) isolated KT was applied in at least one group; (3) comparisons between other techniques were developed; (4) outcomes based on pain, function, disability, or quality of life were analysed. Two reviewers independently extracted data and assessed methodological quality using the Physiotherapy Evidence Database (PEDro) scale. A total of 13 articles met the eligibility criteria, involving 454 participants. Nine of these studies presented upper extremity tendinopathies, and four explored lower extremity tendinopathies. Selected papers ranged from low to high quality, with an average score of 5 on the PEDro scale. According to our findings, there is limited evidence to support KT alone for the treatment of tendinopathies beyond the short-term. Due to the mixed methodological quality and the insufficient number of clinical trials, larger, long-term, high-quality studies are needed to support the theory that tendinopathies can benefit from KT applications.